A Recoverable Complex with Nitrogen‐Rich Double Rings for Hg(II) Sorption. Issue 26 (9th July 2018) - Xu, Wei‐Qin; Lin, Chun‐Cheng; Qiu, Yan‐Xuan; He, Shan; Jiang, Tao; Liu, Xiao‐Jun; Xie, Li‐Jun; Fuhr, Olaf; Fenske, Dieter; Jiang, Ji‐Jun
Abstract: A discrete binuclear copper complex with nitrogen‐rich double rings has been synthesized by ether diffusion method, which was characterized by single crystal X‐ray diffraction. The crystal structure exhibits two connected rings as Arabic numeral "8" shape and stacks each other in the lattice leading to channels for ion sorption. Furthermore, this crystalline material is recoverable and displays high stability in water. The thermal stability has been confirmed by variable temperature powder X‐ray diffraction (VT‐PXRD). Flame atomic absorption spectrometry (FAAS) study has been carried out to confirm the ability of mercury(II) capture from aqueous solution, showing that the porous crystals have good adsorption capacity. The ion sorption kinetic process has been investigated, revealing a pseudo‐second‐order kinetics of mercury(II) adsorption. Abstract : In the current research, we have synthesized a discrete binuclear copper complex with double‐ring, which exhibits high stability in water at room temperature for three months. Six uncoordinated nitrogen atoms in each ring provide the potentially adsorption sites for additional metal ions. The adsorption capacity of Hg(II) on the complex has been evaluated to be 300 mg g −1 . Therefore, this porous material can act as a stable and easily recoverable crystalline adsorbent for Hg(II) in wastewater.